2017
DOI: 10.1111/caje.12253
|View full text |Cite
|
Sign up to set email alerts
|

Do South–South preferential trade agreements undermine the prospects for multilateral free trade?

Abstract: Due to trade diversion, there have been concerns expressed over the proliferation of preferential trade agreements (PTAs) that include South countries. In this paper, we compare welfare across different geographic configurations of bilateral free trade agreements (FTAs) and customs unions (CUs) and examine their implications for the stability of multilateral free trade. While North–North PTAs do tend to yield higher global welfare than South–South PTAs, a single South–South FTA may make free trade more sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…The FTA that excludes the medium-wage country in our model is an example of the opposite outcome. Missios and Yildiz (2017) show that a preferential trade agreement with a high-wage country may harm a low-wage country and that the dynamic incentives to maintain global free trade are weaker when the fallback option is any FTA that includes a high-wage country compared to no agreement.…”
Section: Related Literaturementioning
confidence: 97%
“…The FTA that excludes the medium-wage country in our model is an example of the opposite outcome. Missios and Yildiz (2017) show that a preferential trade agreement with a high-wage country may harm a low-wage country and that the dynamic incentives to maintain global free trade are weaker when the fallback option is any FTA that includes a high-wage country compared to no agreement.…”
Section: Related Literaturementioning
confidence: 97%
“…The developing nations including India have been the part of such trade agreements in the form of the south-south agreements, which involves lower income countries. These are common amongst countries of the Asian and the Latin American region and are considered to be more sustainable (Mayda & Steinberg, 2007;Missios & Yildiz, 2017). Few studies have found that the percentage increase in trade from south-south agreement is more than the north-south agreement (Behar & Cirera-i-Crivillé, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de acordo possui suas vantagens, a busca de maior integração econômica, cooperação intrarregional para maior desenvolvimento econômico, mercados com características e gostos semelhantes e grande probabilidade de formação de acordos de livre comércio. Mas essas relações também possuem suas desvantagens, podem gerar maior desvio de comércio 4 e as uniões aduaneiras formadas por países Sul-Sul tendem a ser mais protecionistas, isto é, imporem uma Tarifa Externa Comum (TEC) superior à aplicada antes da formação do bloco, levando a diminuição do bem-estar dos membros e não membros do acordo (FEENSTRA;TAYLOR, 2017;KRUGMAN, 1991;MISSIOS;YILDIZ, 2017).…”
Section: Problema E Sua Importânciaunclassified